Ancient pottery of the late bronze period in western Siberia and Kazakhstan - Y., Dubyagina (Opción, 2019)
The article discusses the characteristics of ancient ceramics ofthe Late Bronze period in the territory of Western Siberia andKazakhstan. The research methodology includes both traditional forarcheology methods of studying sources, and methods borrowed fromthe arsenal of natural and exact sciences. As a result, the comparativecharacteristics of Western Siberia and Kazakhstan in the late Bronzeperiod clearly show cultural and historical differences in the formationof these communities. In conclusion, fragments of ceramics with theinclusion of small pieces of ore and slag were found.